Trade Credit Contracts - Klapper, Leora; Laeven, Luc; Rajan, Raghuram (Review of Financial Studies, 2012)
We employ a novel dataset on almost 30,000 trade credit contracts to describe the broad characteristics of the parties that contract together and the key contractual terms of these contracts. Whereas prior work has typically used information on only one side of the buyer-seller transaction, this paper utilizes information on both, allowing for the first analysis of buyer-seller pairs. An equally important distinction is that we have multiple contracts for the same buyer or supplier firms, rather than a firm-average response, allowing for the correction of time-invariant firm characteristics that might determine the choice of credit terms. We find that the largest and most creditworthy buyers receive contracts with the longest maturities from smaller suppliers, and that discounts for early payment tend to be offered to riskier buyers.